Nagybérlőből mintagazda. Nádosy Kálmán gazdasági szerepe a dualizmus kori Dél-Dunántúlon - Kaposi, Zoltán (Közép-Európai Közlemények, 2023)
The Hungarian agricultural sector developed significantly in the second half of the nineteenth century. This was the time when the Western technologies and innovations were introduced to the domestic agriculture. However, it was important that trained professionals were working on the domestic large estates of whom had extensive knowledge of the Western manufacturing operations and were up to date on agricultural practices. Our study shows a case like this. Kálmán Nádosy (1832-1913) was coming from a middle-class family. In 1861 he – together with his brother István – leased the bankrupted estate of Szentlőrinc owned by the Prince Esterházy family. While leasing the estate he modernised its operations. His marriage with Mária Jeszenszky helped him to socially integrate into the community of land owners in Somogy and Baranya Counties. Nádosy played a leading role in many business organisation and he was the founder of many of them. After the leasing contract ran out he acquired a part of Helesfa village from the prince, north of Szentlőrinc. Later he also acquired lands in Tótkeresztúr and Görösgal from the heirs of Gusztáv Biedermann. By the end of the nineteenth century his estate comprised more than 2400 hectares of land. He achieved results in viticulture, winemaking, livestock management and forestry. He won numerous street and trade fair awards. He was a great supporter of the Southern Transdanubian Lutheran Church where he worked as a leader for a long time; in the meantime, he also donated to schools and churches.